Fenomena Proses Pengambilan Keputusan Menjadi Lesbi Di Kiaracondong Bandung - Metha Dwi Tamara (Sehat MasadaJurnal, 2019)
Indonesia is a country that still holds the principle of heterosexual relations even though many countries have legalized same-sex marriage. In West Java, there are many lesbian groups. Social institutions indicate that there are at least 185 lesbians in Bandung who are members of 14 small groups of 10-20 people. This research is a descriptive ethnographic study using qualitative data. To obtain qualitative data, researchers prioritize data collection techniques in the form of in-depth interviews, to dig deep information from informants. Family and environmental factors greatly influence an individual's sexual orientation. Conflicts that occur in the family that involve disappointment with the figure of a father coupled with disappointment with the opposite sex become an amplifier for individuals to change their sexual orientation into lesbians. The role of the family and surrounding environment that needs to be improved in paying attention to their children's relationships